A review of website evaluation using web diagnostic tools and data envelopment analysis - Hassan Najadat; Amer Al-Badarneh; Sawsan Alodibat (Institute of Advanced Engineering and Science, 2021)
This paper presents a review of the most recently published works of the use of data envelopment analysis (DEA) in the evaluation of websites of different fields such as healthcare, e-business, e-commerce, and e-government. The evaluation of websites is performed using web diagnostic tools (WDTs). Some studies have evaluated e-government websites using WDTs only, while others integrate them with data envelopment analysis. We summarize each study including the country that was conducted in, the size of data set, inputs to DEA, outputs from DEA, the approach used, the tools used, and the results obtained. It also covers whether there is a use of combination between DEA and data mining or machine learning approaches to classify the efficiency of these websites.